Case study of exploited riparian corridors: rapid assessment of ecological health for riparian buffer width. Issue 1 (2nd January 2016) - Mah, Darrien Yau Seng; Kuok, Kelvin King Kuok; Teo, Fang Yenn
ABSTRACT: Riparian corridors are areas immediately adjacent to flowing waters. They are significant in ecological terms as a transitional zone between aquatic and terrestrial ecosystems. Therefore, conservation of riparian corridors has been gaining significance in river basin management. In this regard, this study has investigated the riparian buffers that fringed the Riveria residential estate in the city of Kuching, Sarawak, examining its structures and health indices in response to the development gradient. The riparian health assessment presented here specifically considers its associated buffer widths, plus the exploration of three attributes, namely human activities, vegetation cover, and groundwater table. The results show that the most appropriate range of buffer width is between 40 and 100 m. Results also suggest that riparian buffer width is a key factor influencing riparian health and functionality.